REFORMS OF EDUCATIO N AND EQUITY - Purvaneckienė, Giedrė; Čiužaitė, Giedrė (Acta Paedagogica Vilnensia, 2010)
Based on analysis of publications, statistics and legal acts, the concept of equity in education, its reflections in Lithuanian legal acts as well as influence of educational reforms on equity is being discussed. Since restoration of Independence in 1990 until 2003, equity, equality, equal opportunities or accessibility were not mentioned in any law on education. In 2003, in the new Law on Education, the term of “equal opportunities” appear for the first time. In 2001, the attempt to increase accessibility of higher education was done. Due to amendments to the Law on Higher education which introduced small tuition fees the numbers of accepted students increased substantially. The new trend of neo-liberal reforms in education was taken after the Parliament elections and formation of new right-wing government in the end of 2008. Green light has been switched on for private educational institutes (from kindergartens to universities). State funding of private educational institutions is gradually expanded at the expenses of state ones. The first results of the reform of higher education connected to the new Law on Science and Studies (2009) are presented. The number of students accepted to the colleges and universities in 2010, in comparison with those accepted in 2008, decreased by 47%. The analysis presented in the article enables to conclude that during educational reforms in Lithuania equity issues were not given serious considerations which led to decrease of equity in Lithuanian higher education.